Literary Appreciation In A Cacophony - Rodiah, Ita; Isnaini, Isnaini; Rahmawati, Isnaini (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
In the cacophony of the digital age, literary appreciation of literary works presents both unique challenges and opportunities. The rapid proliferation of digital platforms has transformed how literature is accessed, consumed, and interpreted. This research explores the evolving landscape of literary appreciation amidst the digital cacophony, highlighting both the advantages and drawbacks. It examines how digital tools and platforms facilitate broader access to diverse literary works, enabling global communities to engage with literature in unprecedented ways. However, it also acknowledges the potential dilution of deep reading practices and critical analysis in favor of quick consumption and superficial engagement. Furthermore, the research discusses strategies to cultivate meaningful literary appreciation in the digital age, emphasizing the importance of promoting deep reading, critical thinking, and cultural understanding. Ultimately, it underscores the enduring value of literature in fostering empathy, cultural appreciation, and intellectual growth amidst the digital noise.